Clobetasol-loaded Dermal Nanostructured Lipid Carriers for the Treatment of Imiquimod Induced Psoriasis in Mice - Veeram, Dr. Jayasankar Reddy (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The aim of current investigation to prepare nanostructured lipid carrier system for topical delivery of clobetasol-loaded nanostructured lipid carriers (NLCs) gel for ease of application on psoriatic dermal and to evaluate its antipsoriatic efficacy compare with conventional clobetasol ointment formulation. Objective: The objective was to develop a nanogel composed of clobetasol (clobetasol -17-propionate [CP])-loaded NLCs (CP-NLCs) and to evaluate its efficiency in imiquimod (IMQ)-induced psoriasis in mice. Materials and Methods: CP-NLCs nanogel was prepared by emulsification and sonication method and optimized by design of experiments. Particle size (PS), polydispersity index (PDI), and entrapment efficiency (EE) were selected as the critical quality attributes. Antipsoriatic efficiency of CP-NLCs nanogel was evaluated by psoriatic area and severity index (PASI) score and histopathological examination in the IMQ-induced psoriasis model. Results and Discussion: Optimized formulation CP-NLCs showed that PS, PDI, and %EE were found to be 95.3 ± 2.56 nm, 0.192 ± 0.011, and 81.3 ± 2.59%, respectively. At the end of 24 h, CP-NLCs gel exhibited slow and prolonged release of CP (74.6 ± 3.82% vs. 35.1 ± 3.58) compared to CP-ointment. Furthermore, it significantly reduced the PASI score with recovery of normalcy of the mice’s skin, while the CP-loaded gel shown signs of hyper and parakeratosis at the end of the study. Conclusion: The formulated CP-NLCs gel can be a promising alternative treatment for psoriasis.